Learning Disabilities Elevate Children's Risk for Behavioral-Emotional Problems: Differences Between LD Types, Genders, and Contexts. (November 2022) - Aro, Tuija; Eklund, Kenneth; Eloranta, Anna-Kaija; Ahonen, Timo; Rescorla, Leslie
Our purpose was to study the frequency of behavioral-emotional problems among children identified with a learning disability (LD). The data were obtained for 579 Finnish children (8–15 years) with reading disability (RD-only), math disability (MD-only), or both (RDMD) assessed at a specialized clinic between 1985 and 2017. We analyzed percentages of children with behavioral-emotional symptoms reaching clinical range (i.e., z score ≥1.5 SD s) and the effects of the LD type, gender, and context (home vs. school) on them. Furthermore, we analyzed the effect of the severity of LD and gender on the amount of behavioral-emotional symptoms reported by teachers and parents. Alarmingly high percentages of children, irrespective of LD type, demonstrated behavioral-emotional problems: more than 37% in Affective, Anxiety, and Attention-Deficit/Hyperactivity Disorder (ADHD) problems. Contextual variation was large, as more problems were reported by teachers than by mothers. The unique effects of gender and LD type were rare, but the results raised concern for those with MD-only, especially boys. The results underscore the need to draw attention to the importance of assessing children with LD for behavioral-emotional problems and emphasize the importance of teachers' awareness of behavioral-emotional problems among students with LD and cooperation among child, teacher, and parents in assessment and support planning.